Foreign Direct Investment (FDI) in the Defence Sector of India : A Review of the Policy Framework - Singh, Shikha; Amin, Shivdasini Singh; Srivastava, Dhruv; Verma, Ridham (Indian Journal of Finance, 2020)
This research paper provided an overview of the existing policy of FDI in the defence sector. It analyzed the effect of liberalization of FDI on the defence sector and examined the benefits India has derived in terms of technological advancements and employment generation. With opening of the defence sector, the Indian government sought to attract major defence players and acquire new technology. India is the third largest military and sixth biggest defence spender and one of the largest importers of conventional defence equipments. The ‘Make in India’ initiative by the Modi government has focused its efforts on increasing indigenous defence manufacturing and to become self-reliant. The study examined the existing framework of FDI in India for the defence sector, its strategic partners, and the collaborations under the ‘Make in India’ programme. It also looked at the pros and cons of the existing policy and discussed their implications and suggested policy recommendations for the future. India aims to be among the top five countries in aerospace and defence, for which it is desirous of reducing dependence on imports and focus on development of indigenous weapon systems. The paper looked at the progress made through the FDI in defence route.